A Cross-sectional Study on Knowledge, Attitude and Practice regarding the use of Iron–Folic Acid Supplementation amongst Antenatal Women of Surendranagar District - Mital Goswami; Roma Dadwani; Hetal Koringa; Dhruvil Vekariya; Nikita Solanki (NMO Journal)
Introduction: As per the National Family Health Survey-5, the prevalence of anaemia amongst pregnant women is 52.2% in India. Iron deficiency anaemia has a negative impact on maternal and child’s health in terms of morbidity as well as mortality. Iron–folic acid (IFA) supplementation is the recommended strategy to prevent its deficiency during pregnancy. Hence, knowledge regarding the use of IFA supplementation has a positive impact on its compliance. Objectives: The aim is to assess knowledge and attitude and to determine practice regarding the use of IFAS amongst antenatal women of Surendranagar district. Materials and Methods: A community-based cross-sectional study was conducted in Surendranagar district. The sample size was 260, which was calculated based on the pregnancy registration rate. To achieve this sample size, 26 subcentres were selected randomly. Data were collected using predesigned, pretested and semi-structured questionnaires. Results: Out of the total study participants, more than half were between the age group of 22–24 years (57.7%) and the mean age was 26.94 ± 5.15. Almost all were aware of IFA supplementation (96.2%), and nearly three-fourths (75.5%) were taking it. Of pregnant women who were taking IFA tablets amongst them 88.2% were taking it regularly. They were aware that lemon increases its absorption (61%), but it should not be taken immediately after a meal (62%). Majority of women felt that it helps to improve their health during pregnancy and improve their child’s health (90%). Conclusion: Majority of women amongst study participants were aware of IFA supplementation and taking it regularly. However, knowledge regarding its absorption was observed to be low amongst them.